2011
DOI: 10.1007/s12230-011-9195-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Colletotrichum Coccodes to Selected Fungicides Using a Plant Inoculation Assay and Efficacy of Azoxystrobin Applied by Chemigation

Abstract: A plant inoculation assay was developed and used to evaluate fungicide efficacy and application timing for reduction of infection of potato stems by Colletotrichum coccodes. Incidence of infected stems treated with azoxystrobin, pyraclostrobin, fluoxastrobin, and mandipropamid + difenoconazole was significantly less than the non-treated control plants when fungicides were applied prior to inoculation. However, fungicide application after inoculation did not significantly reduce infection. Chlorothalonil and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
0
5
1
1
Order By: Relevance
“…However, black dot levels were not reduced when azoxystrobin was applied at planting in a previous study (9) and incidence of black dot was observed not to be affected with an application at planting in the present study. Reductions in black dot levels were incon sistent when azoxystrobin was applied by chemigation in a previous study (21) and were inconclusive in this study. The one exception, field U5W, was rotated out of po tatoes for 15 years and had a black dot incidence of 9%.…”
Section: Discussioncontrasting
confidence: 66%
“…However, black dot levels were not reduced when azoxystrobin was applied at planting in a previous study (9) and incidence of black dot was observed not to be affected with an application at planting in the present study. Reductions in black dot levels were incon sistent when azoxystrobin was applied by chemigation in a previous study (21) and were inconclusive in this study. The one exception, field U5W, was rotated out of po tatoes for 15 years and had a black dot incidence of 9%.…”
Section: Discussioncontrasting
confidence: 66%
“…En términos generales, la aplicación a los 0 ddi fue más eficaz. Otros autores (Serey et al, 2007;Della-Rocca et al, 2011;Días y Latorre, 2013) también han observado, para otros patosistemas, incluidas otras especies de Colletotrichum (MacKenzie et al, 2009;Ingram et al, 2011), una mayor eficacia de fungicidas de los grupos aquí evaluados cuando se aplicaron en pre-inoculación. Sin embargo, el combate de la enfermedad se reduce conforme aumenta el tiempo que transcurre entre la aplicación del fungicida y la inoculación (Poblete y Latorre, 2001;Mondal et al, 2007).…”
Section: Resultados Y Discusiónunclassified
“…[1][2][3] It is primarily found on Solanaceae, Fabaceae and Cucurbitaceae, and is particularly destructive as black dot disease in potatoes and anthracnose on tomatoes. 4,5 There are more than one hundred known isolates of this fungus in Israel. C. coccodes is difficult to control and it is considered as seed tuber and soilborne.…”
Section: Introductionmentioning
confidence: 99%